Fragile X Premutation Associated Conditions (FXPAC) - Johnson, Kirsten; Herring, Jonathan; Richstein, Jörg (Frontiers in Pediatrics, 2020)
The European Fragile X Network (EXFN) proposes that Fragile X Premutation Associated Conditions (FXPAC) be adopted as a universal term covering any condition linked to the Fragile X premutation. To date, there has not been an umbrella term assigned to premutation carriers, though several defined conditions which affect some premutation carriers, namely Fragile X Primary Ovarian Insufficiency (FXPOI) and Fragile X Tremor Ataxia Syndrome (FXTAS), are now commonly accepted. An overarching term covering all FX premutation conditions will help doctors in determining how the premutation might be affecting their patient; and encourage researchers to explore the interrelationships of the various conditions affecting premutation carriers. Further, there are ongoing discoveries about physical and psychological issues faced by premutation carriers, and a new term helps encompass all of these burgeoning developments.